Modelling of a novel technique to improve the visualisation of implanted fiducial markers for intra-fraction MV imaging of prostate VMAT targets. (23rd July 2021) - Aland, Trent; Jones, Mark; Aho, Jari; Kairn, Tanya; Trapp, Jamie
Abstract: Purpose . This study explored a novel technique to improve the MV imaging based fiducial visibility for a cohort of prostate radiotherapy patients, without compromising the original treatment plan. The study also compared these results to visibility using single MLC control points, as well as short arcs. Methods . Geometric data from 68 prostate radiotherapy treatments, each with implanted gold fiducials, was retrospectively analysed. Fiducials were contoured for each patient, and conventional and SBRT treatment plans were generated using a VMAT technique. Using an in-house script, fiducial contours were projected onto the VMAT MLC control points. Resulting data was assessed to determine whether the fiducial contours were theoretically visible for single MLC control points and groups of MLC control points (short arcs), both being surrogates for intra-fraction MV imaging. Using this data, a theoretical quadrant technique was investigated that assessed the region surrounding each fiducial to determine if visualisation would theoretically improve. Results . Using a conventional treatment type, mean fiducial visibility for single MLC control points across the patient cohort ranged from 2.5% up to 17.8%. For SBRT, fiducial visibility ranged from 1.8% up to 19.7%. For short arcs, fiducial visibility for conventional treatment types ranged from 5.9% up to 20.7%. For SBRT, fiducial visibility ranged from 4.6% up to 23.1%. When the novel fiducial quadrant technique was used, theoretical visibility improved two-fold, from 22.7% up to 52.5% and from 24.7% up to 55.3% for conventional and SBRT treatment types respectively. Conclusions . Fiducial visibility was assessed for a cohort of VMAT prostate patients. Using the novel quadrant technique, it was demonstrated that theoretical visualisation and localisation of the implanted fiducials could be improved two-fold, without sacrificing treatment plan quality.